Economic regulation and state interventions: Georgia's move from neoliberalism to state managed capitalism - Christian Timm (PFH Private Hochschule Göttingen, 2013)
This paper explores the change in the Georgian economic policy from neo-liberalism to state-managed capitalism that occurred between 2003 and 2012. Centering on the distributive effect of institutions, the analysis reveals the underlying dynamic of that policy change. The paper argues that the introduction of a radical liberal regulatory environment contributed significantly to the development of informal state interventions in the economy. However, the Russian-Georgian war in 2008 destroyed the increasingly undermined FDIoriented liberal development model and forced the government to alter its economic policy. By relying on established informal instruments of intervention and the development of an official economic development agenda, a specific form of state-managed capitalism evolved in Georgia in the period that followed.
Keywords: 330